EFFICIENCY OF IMMUNOCORRECTION WITH MEDICAL OZONE IN PROTRACTED PURULENT INFLAMMATORY DISEASES AFFECTING SOFT TISSUES IN THE PATIENTS OF SENIOR AGE GROUP - T. I. Vitkina (SPb RAACI, 2014)
Abstract. We performed a clinical and immunological study of patients from senior age group suffering with protracted purulent inflammation of soft tissues in maxillo-facial area. The patients underwent either common medication, or combined treatment including ozone therapy. Application of medicinal ozone, along with basic treatment schedule, resulted into more marked and rapid normalization of non-specific resistance markers, Т-cell immunity. This approach allows of reducing the terms of inpatient care and variety of possible complications. (Med. Immunol., 2008, vol. 10, N 2-3, pp 277-282).